Evaluation of a lower-extremity robotic exoskeleton for people with knee osteoarthritis. Issue 5 (3rd September 2022) - McGibbon, Chris; Sexton, Andrew; Jayaraman, Arun; Deems-Dluhy, Susan; Fabara, Eric; Adans-Dester, Catherine; Bonato, Paolo; Marquis, Francois; Turmel, Sylvie; Belzile, Etienne
ABSTRACT: A multi-site study was conducted to evaluate the efficacy of the Keeogo™ exoskeleton as a mobility assist device for use in the clinic and at home in people with knee osteoarthritis (KOA). Twenty-four participants were randomized in a two-stage cross-over design that evaluated the immediate effects of using the exoskeleton in the clinic and the cumulative effects of training and home use. Immediate effects were quantified by comparing 1) physical performance with|without (W|WO) the device during a battery of mobility tests, and 2) physical activity levels at home (actigraphy) for one month, two weeks W|WO the device. Cumulative effects were quantified as change in physical performance W and WO over time. WOMAC and other self-report scales were measured and usability assessed. There were no immediate effects on physical performance or physical activity at home; however, there were cumulative effects as indicated by improved stair time ( p = .001) as well as improved WOMAC pain ( p = .004) and function ( p = .003). There was a direct relationship between improved physical function and improved WOMAC pain (r = −.677, p < .001) and stiffness (r = .537, p = .007). Weight and battery life were identified as important to usability. A full-scale RCT with more participants, longer study period, and better usage monitoring is warranted.